PENGARUH FAKTOR-FAKTOR KEUANGAN TERHADAP AUDIT REPORT LAG PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Prabowo, Pramudia; Zulfikar, Zulfikar (LPPM Universitas Bina Bangsa, 2024)
The increasing number of companies in the form of Go Public is a sign that the development of activities on the Indonesia Stock Exchange (IDX) is increasing, this will trigger a high demand for effective and efficient financial statement audits. Companies that have gone public have an obligation to submit financial reports in a timely manner. Delays in submitting financial reports are caused by audit report lag. Financial factors such as company size, profitability, leverage, liquidity, earnings per share, and financial distress are indicated to be the cause of audit report lag. So that these financial factors require special attention so that the submission of audited financial reports is timely. This study aims to determine the effect of company size, profitability, leverage, liquidity, earning per share, and financial distress on audit report lag in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2020-2022. The population in this study are all manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2020-2022. The sampling technique in this study used purposive sampling method, so that a sample of 86 companies was obtained with a total of 217 observations. The results showed that company size and profitability had a significant negative effect on audit report lag, leverage and liquidity had no effect on audit report lag, and earning per share and financial distress had a significant positive effect on audit report lag